Cultural sociology : an introduction - Back, Les, 1962- (Chichester, West Sussex : Wiley-Blackwell, 2012)
'The book also sets out the key antecedents contributing to the emergence of cultural sociology and presents students with a firm grounding in theoretical and methodological principles applied by cultural sociologists in their work'--
Includes bibliographical references and index.
Keywords: Culture; Sociology